COVID-19 VACCINE SRATEGIES AND POLICIES IN UPPER-MIDDLE INCOME AND UPPER INCOME COUNTRIES IN ASEAN - Zurlina, Cut Falia (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
Covid-19 vaccination is one of an effort to prevent and break the chain of transmission. Until July 2024, Covid-19 positive cases reached 775.686.716 with total 7.054.093 deaths. Every country has their own strategies and policies to reduce the number of transmissions. The purpose of this study is to analysing vaccination strategies and policies in ASEAN country members that categorized in UIC and UMIC group, Brunei Darussalam, Singapore, Malaysia, Indonesia, and Thailand. The method in this study is using literature study and documenta analysis that related to this topic which can be accessed publicly, such as statistical data and government documents. Based on the results, the five countries have some similarities in vaccination strategies and policies. This happened because of there is a collaborative action plan within ASEAN country members and be adapted by all countries. However, there are still several countries that have not complied vaccination target of WHO, 70%.